CONDITIONING AND SAFE STORAGE OF COWPEA SEEDS USING PLASTIC HERMETIC BAGS - Tarek FOUDA; Mohamed ELKHOLY; Adel Helal ELMETWALLI; Dalia SALEH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Most important feature of the storage systems is to preserve the integrity of the grain for a given period with minimal loss in quality and quantity. The main objective of this study was to evaluate the effect of seed conditioning prior to storage process using infrared heating at the optimum radiation intensity of 882.67W/m2 and exposure time of 15 min and the ultraviolet radiation at radiation intensity of 3.538mW/cm2 and exposure time of 40 min on storability of cowpea seeds using different types of plastic hermetic bags in comparison with pp woven bags. The changes in cowpea seeds quality during storage of pre-treated cowpea seeds in terms of moisture content, protein content, total microbial count and insect detection were also determined. The results show that, the moisture content of seeds stored in pp woven bags increased in contrast with both types of studied hermetic bags, oxygen concentration for hermetic bags decreased during storage period and carbon dioxide increased unlike pp woven bag, The rate of seeds infection with microorganisms and weevils was lower for the samples stored in both types of hermetic bags and crude protein content of seeds stored in hermetic bags reduced at a very slight rate in comparison with that stored in woven bag.